Atributos microbiológicos do solo em sistemas de manejo de longa duração - Barbosa, Marcelo de Andrade [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Soil management systems, as well as the application of fertilizers may promote changes on microorganism activity in the soil. In this regard, four experiments were performed in order to evaluate the microbial respiration (MR), the microbial biomass carbon (MBC), metabolic quotient (q CO2), total organic carbon (TOC), total nitrogen (TN), microbial biomass nitrogen (NBM), and the enzymatic activity of urease (UEA), dehydrogenase (DEA) and amylase (AEA) in soils from areas with a history of management and fertilization (cattle manure and urea). The first experiment consisted of planting maize as a summer crop in conventional tillage system with urea fertilization (CT U), at the rates: 0.90 and 180 kg ha-1 N; the second, of planting maize in summer in conventional tillage fertilized with cattle manure (CT M), at the rates: 0.5 and 60 Mg ha-1; and the third and fourth consisted of no-tillage with maize/maize (NT M/M) and legumes/maize (NT L/M) cover crops, respectively, both fertilized with urea, at the same rates of the first experiment. The no-tillage system with legumes/maize cover crops is the one that best provides favorable conditions for microorganism development in the soil. The conventional tillage fertilized with cattle manure has a higher microbial activity compared to the conventional tillage fertilized with urea. The N rates in the form of urea provide decreased microorganism activity in no-tillage system with legumes/maize cover crops and increase in no-tillage with maize/maize cover crops. The microorganism activity in the soil increases with increasing rates of cattle manure

Sistemas de manejo do solo, assim como a aplicação de adubos podem promover alterações sobre atividade de microrganismos no solo. Nesse sentido, quatro experimentos foram executados com o objetivo de avaliar a atividade respiratória microbiana (ARM), o carbono da biomassa microbiana (CBM), o quociente metabólico (q CO2), o carbono orgânico total (COT), o nitrogênio total (NT), o nitrogênio da biomassa microbiana (NBMS), e a atividade enzimática da urease (AEU), desidrogenase (AED) e amilase (AEA) em solos provenientes de áreas com históricos de manejo e adubação (esterco bovino e ureia). O primeiro experimento foi constituído por plantio de milho como cultura de verão em sistema convencional com adubação com ureia (PC M), nas doses: 0, 90 e 180 kg ha-1 de N; o segundo, por plantio de milho no verão em sistema convencional adubado com esterco bovino (PC E), nas doses: 0, 5 e 60 Mg ha-1; e o terceiro e quarto, por plantio direto com sucessão milho/ milho (PD M/M) e leguminosa/ milho (PD L/M), respectivamente, ambos adubados com ureia, nas mesmas doses do primeiro experimento. O sistema de plantio direto com sucessão leguminosa/ milho é o que melhor propicia condições favoráveis ao desenvolvimento de microrganismos no solo. O plantio convencional adubado com esterco bovino apresenta maior atividade microbiana em relação ao plantio convencional adubado com ureia. As doses de N na forma de ureia proporcionam decréscimo da atividade de microrganismos em sistema de plantio direto com sucessão leguminosa/ milho e acréscimo em plantio direto com sucessão milho/ milho. A atividade de microrganismos no solo aumenta com o incremento das doses de esterco bovino
Keywords: Microorganismos do solo; Plantio direto; Análise enzimática; Solos - Qualidade; Solos - Manejo; Enzymes